Working As A Law Enforcement Officer In Your Community - Daniel E. Harmon
Police and other law enforcers are often seen around towns and cities, helping to keep the peace and enforcing the laws. This informative resource offers an overview of many of the common law-enforcement careers, from beat cops and investigators to security guards and probation officers. Each chapter provides insight into the exciting aspects of the job and brings to light any potential challenges, drudgery, and downsides. Readers will learn what steps to take during high school and after, including classes, internships, and college degrees. This book will get readers started learning about careers in law enforcement that keep every community running smoothly.